Sebuah Studi Ritel Minuman Kekinian: Masihkah Experiental Marketing Berpengaruh pada Kepuasan? - Rilantiana, Rosa; Nugraheni, Roostikasari; Wardhana, Aditya Narendra (Universitas Medan Area, 2023)
The aim of the research is to find which components experiental marketing significantly influence satisfaction becaused The food and beverage industry is experiencing changes in situations, experiences during and after the Covid 19 pandemic. There is a need for studies that support the validity of various customer satisfaction factors. On the other hand, the emergence of innovative and creative products that are able to shift trends according to consumer appeal. Through a quantitative research approach, 170 respondents' data was processed using SEM with the STATA 14.2 program. The results show that there is a direct influence of experimental marketing consisting of sense, feel, act, think and related variables on customer satisfaction. More deeply, researchers also found that value is an intervening variable in the influence of sense, act, think and related to customer satisfaction that focuses on contemporary coffee businesses.